(untitled) (Research, Society and Development, 2021)
Objective: This study aimed to determine the repeatability and reproducibility of a topographic system for evaluating the spine in students. Methods: Thirty-seven students participated in this study. Participants were positioned with their backs facing the system, in orthostatic posture, with bare backs. The spinous processes of the seventh cervical vertebra (C7) and second sacral vertebra (S2), and the right and left posterior superior iliac spine (PSIS) were marked. Each student was evaluated five times, once on the first day and four times on the second day. The following variables were used for evaluation: kyphosis angle, lordosis angle, trunk length, and anterior and lateral perturbations. SPSS 17.0 (IBM, Armont, NY, USA) was used for performing statistical analyses, which included descriptive analysis, Intraclass Correlation Coefficient (ICC), and one-way ANOVA, with a significance level of 0.05. Results: topographic system showed excellent values, and a positive correlation was observed with reference to the ICC of reproducibility and repeatability for all analyzed variables. Conclusion: These results show that this system can be used to diagnose postural changes, and to estimate thoracic kyphosis and lumbar lordosis angles. It can also be used for providing additional information on the positioning of the surface of the back.